Acacia dealbata invasion and clearing in Upper Tsitsana communal areas of South Africa: human perceptions and ecological impacts - Coka, Nwabisa (Rhodes University, Faculty of Science, Department of Environmental Science)
The number of invasive alien plants in South Africa and globally continue to increase mostly due to increased human movement and climate change. It is estimated that approximately 10 000 hectares of South Africa's terrestrial land is invaded by invasive alien species. Recent studies have reported that invasion by invasive alien plants cost South Africa billions of Rands every year through loss of water and ecosystem services. Although much has been done to understanding invasion trends, patterns, and processes in South Africa, little is knowns regarding human benefits linked to alien plant invasion as well as human perceptions regarding management interventions, particularly clearing by the national Working for Water programme. This thesis took a socio-ecological approach to assess (i) local people perceptions and knowledge of Acacia dealbata invasion and clearing, and (ii) extent of grazing grass diversity and composition recovery following A. dealbata clearing. To answer the above-mentioned objectives, both qualitative (face-to-face interviews) and quantitative (vegetation surveys) methods were used in grasslands located in upper Tsitsana catchment, South Africa. Results from the 165 interviews conducted in six villages show that most villagers are aware of A. dealbata in the area, but do not know that it is an invasive alien plant. Respondents accrue several benefits from the plant that include firewood (98% across all villages), construction pools (34% across all villages), and shade (3% across all villages). Respondents identified several costs associated with A. dealbata invasion, such as roots damage to houses (37% across all villages), hindering growth of crops (15% across all villages), and takes up yard space (29% across all villages). Most of the villages ranked the effects of A. dealbata on grazing as highly severe. Villages indicated that the Working for Water clearing programme presents them with socio-economic benefits such as employment and money. Some villagers noted that the clearing of A. dealbata in the area restores grazing grass (62% across all villages) and water (32% across all villages). Based on these interview survey results, the study concludes that A. dealbata has both costs and benefits that support local people's livelihoods; therefore, its management should consider views for local users. Grass surveys conducted in 1 m2 quadrats that were replicated 15 times across four paired A. dealbata cleared and grassland sites showed that the removal of A. dealbata facilitates the recovery of native grasses. Of the 14 different grazable grass species that were identified across all quadrats only one (Bulbostylis sp.) is not palatable to livestock. Although grass cover was significantly (p < 0.05) higher in the grasslands than the cleared patches, grass richness was significantly (p < 0.05) higher in the cleared patches an indication that recovery of different grasses is taking place. Based on these vegetation survey results; the study concludes that recovery of grazing grasses after A. dealbata clearing four years ago is following a positive trajectory as the cleared sites are looking like the grassland sites. Overall, the study recommends that management of A. dealbata in Tsitsana landscape requires a socio-ecological approach to understand user benefits whilst at the same time developing measure to control the plant. The study has provided evidence that A. dealbata clearing facilitates passive restoration of grazing grass and local villages are aware of these restoration benefits.
Keywords: Restoration ecology -- South Africa -- Eastern Cape; Acacia dealbata; Invasive plants -- South Africa -- Eastern Cape; Working for Water Programme; Invasive plants Control -- South Africa -- Eastern Cape